Economic globalisation, institutions and environmental quality in Sub-Saharan Africa - Claire E. W. Yameogo; Joseph Ayoola Omojolaibi; Risikat O. S. Dauda (Research in Globalization, 2021)
This paper explores the relationship between economic globalisation and environmental quality by incorporating institutions as the determinant of this relationship for Sub-Saharan Africa (SSA). The study deploys the technique of generalised methods of moments to assess data spanning the period 2002-2017. Findings indicate that regulatory quality positively impact environmental degradation while economic globalisation and control of corruption negatively affects environmental degradation in SSA. Furthermore, the results show that economic growth and government effectiveness negatively affect the environment while the institution index positively affects the environment in the region. It was also found that the interaction between economic globalisation and institution has negative and significant effects on environmental pollution, thus contributing to environmental quality. Consequently, the study recommends that governments should ensure the emergence of strict trade-environmental regulations.
Keywords: Q01; Q53; Q55; Q58; 330; Economic globalisation; Environmental quality; Institutions; Sub-Saharan Africa